Respostas

2013-10-27T00:47:56-02:00
5x + 3 = 253x - 1
5x - 253 x = - 1 - 3
- 248x = - 4           x(-1)
248x = 4
   x = 4/248 = 1/62

log 2 8 = x ===> 8 = 2^x
                          2³  = 2^x
                             3 = x ou x = 3

log 3 81 = x ==> 81 = 3^x
                           3^4 = 3^x
                              4 = x  ou x = 4
1 5 1
  • Usuário do Brainly
2013-10-27T11:31:17-02:00
A) 5x + 3 = 253x - 1
5x - 253x = - 1 - 3
-248x = - 4 .(-1)
248x = 4
x = 4/248 (simplifique por 4)
x = 1/62

b) log2 8
2^x = 8
2^x = 2^3
x = 3

c)log3 81
3^x = 81
3^x = 3^4
x = 4